Föryngring i stormfälld rekreationsskog : en jämförelse mellan föryngring i produktions-, rekreation/produktion och rekreationsskog. - Höglund, Kerstin (SLU/Southern Swedish Forest Research Centre, 2007)
When the storm Gudrun hit Sweden on the 8th and 9th of January, many recreational forests in southern Sweden blew down. For this reason there is a demand for new regeneration methods as to how these storm-felled areas should be regenerated and with what species.